Development of a Low-Cost Spectrophotometer for Protein Determination Using the Lowry Method - Salsabilla, Lestha Aurel; Hermawan, Dadan; Diastuti, Hartiwi; Anggraeni, Mekar Dwi; Fatoni, Amin (Indonesian Journal of Chemistry, 2026)
Affordable and accessible laboratory equipment is increasingly crucial, particularly in resource-limited settings. This research presents the development of a cost-effective spectrophotometer using an Arduino microcontroller and a TSL2591 light sensor to quantify protein concentration via the Lowry method. The device employs a 750 nm LED and a 3D-printed PLA case to house the components. Casein was used for calibration, yielding a linear detection range of 100–700 ppm with a high correlation coefficient (r = 0.9991). The limit of detection (LOD) and limit of quantification (LOQ) were 18.05 and 60.16 ppm, respectively. Precision was confirmed with a HORRAT value of 0.982. Accuracy was validated using the Wilcoxon Signed-Rank test, which showed no significant difference between the fabricated device and a commercial UV-vis spectrophotometer (p = 0.779). These findings support the reliability and reproducibility of the device for protein quantification. The project’s open-source nature encourages further development and application in educational, clinical, and field settings. This innovation supports the development of accessible, low-cost biochemical analysis tools.